證實:
E(X)=nNM
E(X2)=k=0∑min{n,M}k2(nN)(kM)(n−kN−M)=k=0∑min{n,M}k2k!(M−k)!M!(n−kN−M)N!n!(N−n)!=k=1∑min{n,M}k(k−1)!(M−k)!M!(n−kN−M)N!n!(N−n)!=k=1∑min{n,M}(k−1)(k−1)!(M−k)!M!(n−kN−M)N!n!(N−n)!+k=1∑min{n,M}(k−1)!(M−k)!M!(n−kN−M)N!n!(N−n)!=k=2∑min{n,M}(k−2)!(M−k)!M(M−1)(M−2)!(n−kN−M)N!n!(N−n)!+k=0∑min{n,M}kk!(M−k)!M!(n−kN−M)N!n!(N−n)!=M(M−1)N!n!(N−n)!k=2∑min{n,M}(k−2M−2)(n−kN−M)+E(X)=M(M−1)N!n!(N−n)!(n−2N−2)+nNM(範德蒙恆等式Cm+nk=i=0∑kCmiCnk−i)=M(M−1)N(N−1)n(n−1)+nNM=nNM[N−1(M−1)(n−1)+1]
∴D(X)=E(X2)−[E(X)]2=nNM[N−1(M−1)(n−1)+1]−(nNM)2=nNM(N−1Mn−M−n+1+N−1−nNM)=nNM[N(N−1)MNn−MN−Nn+N2−MNn+Mn]=nNM[N(N−1)N(N−M)−n(N−M)]=nNM[N(N−1)(N−M)(N−n)]=nNM(1−NM)(N−1N−n).